Joint Exposure to Multiple Air Pollutants, Genetic Susceptibility, and Incident Dementia: A Prospective Analysis in the UK Biobank Cohort - Zhang, Shuo; Cao, Hongyan; Chen, Keying; Gao, Tongyu; Zhao, Huashuo; Zheng, Chu; Wang, Ting; Zeng, Ping; Wang, Ke (International Journal of Public Health, 2024)
Objectives: This study aimed to evaluate the joint effects of multiple air pollutants including PM2.5, PM10, NO2 and NOx with dementia and examined the modifying effects of genetic susceptibility.Methods: This study included 220,963 UK Biobank participants without dementia at baseline. Weighted air pollution score reflecting the joint exposure to multiple air pollutants were constructed by cross-validation analyses, and inverse-variance weighted meta-analyses were performed to create a pooled effect. The modifying effect of genetic susceptibility on air pollution score was assessed by genetic risk score and APOE ε4 genotype.The HR (95% CI) of dementia for per interquartile range increase of air pollution score was 1.13 (1.07 1.18). Compared with the lowest quartile (Q1) of air pollution score, the HR (95% CI) of Q4 was 1.26 (1.13 1.40) (Ptrend=2.17×10 -5 ).Participants with high air pollution score and high genetic susceptibility had higher risk of dementia compared to those with low air pollution score and low genetic susceptibility.Discussion: Our study provides evidence that joint exposure to multiple air pollutants substantially increases the risk of dementia, especially among individuals with high genetic susceptibility.